MicroFluidic based pre-concentration system for microbial sample preparation in the water - Zheng, Ting Ting (2015)
Based on the research done on waterborne disease, it is the second leading causes on fatal or death to children’s health. The cause of the waterborne disease is due to the existence of protozoa in the drinking water. The protozoa can be spread speedily and contaminate the water system due to its ability to stay in water for a long period of time waiting for host who could have accidentally digest it. Although there are various water treatment in the market, but for protozoa such as cryptosporidium it could withstand this treatment and continue to contaminate the treated water. Hence, to ensure the drinking water is free from protozoa, a system that could trap and detect the existence of protozoa in the water is required. In this project, in-line micro-fluidic microbial detection system is introduced. The system consists of two sub-system, pre-concentration and detection system. Pre-Concentration system is capable of gathering the particles by concentrating the water into a smaller volume in a minimum time needed for protozoa detection. The detection system is capable of identifying and categorizing protozoa. With this system, minimum labor force and time is needed to complete a full course of laboratory test needed to check for existence of protozoa in drinking water. Experiments on performance efficiency will be conducted on the pre-concentration system.